A NASICON‐Type Positive Electrode for Na Batteries with High Energy Density: Na4MnV(PO4)3. Issue 4 (27th August 2018) - Chen, Fan; Kovrugin, Vadim M.; David, Rénald; Mentré, Olivier; Fauth, François; Chotard, Jean‐Noël; Masquelier, Christian
Abstract: The mixed Mn 2+ /V 3+ Na‐super‐ionic‐conductor (NASICON) cathode material Na4 MnV(PO4 )3 is prepared by solid‐state reaction at 800 °C under argon. When used as a positive electrode in Na batteries, this material can exchange three electrons for two transition metals, that is, yielding a high gravimetric capacity of 156 mAh g −1 on charge when the upper cutoff voltage is set to 4.3 V versus Na + /Na. Operando X‐ray diffraction during battery operation is performed and it is shown that the mechanisms of Na + insertion/extraction are single or biphasic depending on the electrochemical cycling conditions. Abstract : The Na‐super‐ionic‐conductor (NASICON)‐based material Na4 MnV(PO4 )3 allows the extraction of 3Na + formula unit −1 at relatively high voltage. Depending on the upper cutoff voltage, structural rearrangements occur within the framework, which modify the nature of the associated electrochemical extraction/insertion reactions. This study identifies the crystal structures of the Na3 MnV(PO4 )3 and NaMnV(PO4 )3 new compositions.